Analyzing ethical considerations and research methods in children research - Mukhlash Abrar; Ezis Japar Sidik (Intelektual Pustaka Media Utama, 2019)
Research involving children and young people has a particular challenge in comparison to research involving adults. Of this particular challenge is related to the issues of ethical considerations and research methods that the researchers have to commit when conducting research. These are two essential research components and integrally linked to one another because they determine the quality and integrity of the research being conducted. These issues require thorough consideration and implemented differently from the research involving adults. Therefore, this paper aimed to discuss the ethical issues and research methods in researching children and critically evaluate these issues from the research practices by taking the cases of the articles in Teaching English to Speakers of Other Languages. Three articles were selected for further analysis to identify the ways the authors address these issues in their articles. The findings indicated that the authors mainly reported common ethical principles, such as voluntary participation and anonymity, but did not explicitly outline the ethical procedures specific for their children participation in their papers. There was also no indication that they employed appropriate methods to work with children such as using child-friendly methods encouraging children’s participations and giving them space to express opinions and thoughts.